2013
DOI: 10.20453/rmh.v7i2.524
|View full text |Cite
|
Sign up to set email alerts
|

Características epidemiológicas de los pacientes con paraparesia espástica tropical (PET) asociada a infección por HTLV-1 en Lima, Perú.

Abstract: Objetivo: Describir las características epidemiológicas de la paraparesia espástica tropical asociada a infección por HTLV-1. Material y métodos: Se realizó un estudio descriptivo de 61 pacientes consecutivos con paraparesia espástica tropical (PET) asociada a HTLV1. Los casos fueron evaluados prospectivamente en dos instituciones de Lima (Instituto de Medicina Tropical "Alexander Von Humboldt" y el Servicio de Neurología del Hospital Nacional Guillermo Almenara Irigoyen) entre agosto de 1989 y noviembre de 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Interestingly, in the report of 165 Peruvian cases of HAM/TSP, Andean origin, defined as we did, was associated with the disease. 16 No studies of HAM/TPS have been done in the Peruvian Andes; such studies could provide evidence of the natural history of the disease in the Quechua population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the report of 165 Peruvian cases of HAM/TSP, Andean origin, defined as we did, was associated with the disease. 16 No studies of HAM/TPS have been done in the Peruvian Andes; such studies could provide evidence of the natural history of the disease in the Quechua population.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was also described in a case series of 61 patients with HAM/TSP done in Lima, where more than 50% of the patients were born in an Andean region. 16,17 Of note, data from the 1993 National Census 18 indicated that the highest rate of lower-limb disability, which can be observed in HAM/TSP cases, occurred in the southern Andean regions of Peru, and, as also described for HAM/TSP, was more frequent in women than in men.…”
Section: Introductionmentioning
confidence: 89%